Proceedings 23rd Annual Conference on Local Computer Networks. LCN'98 (Cat. No.98TB100260)
DOI: 10.1109/lcn.1998.727663
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of reliable multicast protocols using the network simulator ns-2

Abstract: Reliable multicast protocols on top of the MBone are presently subject to intensive research. In the past, numerous protocols have been developed and their respective performance been analysed. Little progress has been made, though, to compare different approaches. In this paper, we use the network simulator ns-2 to evaluate the performance of three protocols, namely Scalable Reliable Multicast (SRM), Multicast File Transfer Protocol (MFTP) and an enhanced version of the latter, called Multicast File Transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…ns-2: Network Simulator-2 (ns-2) [46] is an open source, discrete event network simulator for both wired and wireless networks. In ns-2, arbitrary network topologies can be defined that are composed of routers, links and shared media [47]. The physical activities of the network are processed and queued in the form of events, in a scheduled order.…”
Section: Simulation Toolsmentioning
confidence: 99%
“…ns-2: Network Simulator-2 (ns-2) [46] is an open source, discrete event network simulator for both wired and wireless networks. In ns-2, arbitrary network topologies can be defined that are composed of routers, links and shared media [47]. The physical activities of the network are processed and queued in the form of events, in a scheduled order.…”
Section: Simulation Toolsmentioning
confidence: 99%
“…Comparison of reliable multicast protocols using the NS-2 simulator are available in [31]. It appeared in 1998, which is also the year during which the IETF adopted RFC 2357 [42] on that same topic.…”
Section: Ns-2 As a Tool For Designing Internet Protocolsmentioning
confidence: 99%
“…In [35], authors compared three reliable multicast protocols, namely SRM, MFTP, MFTP/EC, by using Network Simulator-2. They showed that, SRM floods the network with repair packets substantially when loss rates are high, resulting in even higher loss rates due to additional traffic.…”
Section: Literature Surveymentioning
confidence: 99%